Anti-amebic effects of Chinese rhubarb (Rheum palmatum) leaves' extract, the anthraquinone rhein and related compounds. Issue 4 (April 2020) - Espinosa, Avelina; Paz-y-Miño-C, Guillermo; Santos, Yoly; Ma, Hang; Nadeau, Michael; Seeram, Navindra P.; Rowley, David C.
Abstract: Entamoeba histolytica infects 50 million people worldwide and causes 55 thousand fatalities every year. Current anti-amebic drugs (e.g. paromomycin) work either at the level of the intestinal lumen (where trophozoites proliferate via cell divisions) or on the invasive trophozoites that have penetrated the gut or colonized internal organs (e.g. metronidazole). Some of these drugs are highly toxic to patients, have generated trophozoite resistance, or caused mutations and cancer in laboratory animals. Thus, alternative anti-amebic compounds need to be identified to minimize the side effects (on patients) or resistance (by amebas) to current treatments. The literature suggests that anthraquinones (chemicals found in medicinal plants) have antibacterial, antiparasitic, anti-inflammatory and antioxidant properties. Here we provide experimental evidence that Chinese rhubarb ( Rheum palmatum ) leaves' extract (rich in the anthraquinone rhein) inhibits E. histolytica trophozoite growth in vitro . In addition, from a set of ten isolated/synthetic anthraquinones (which we suspected to have anti-amebic properties), four analogs (rhein; AHHDAC = 1-amino-4-hydroxy-9, 10-dioxo-9, 10-dihydro-anthracene-2-carboxylic acid; unisol blue AS; and sennoside B) efficiently inhibited amebic growth at EIC50 concentrations comparable to metronidazole. The mechanism of action of these compounds still needs to be determined, although anthraquinones might enhance the production of toxic oxygen metabolites as it has been suggested for various protists (e.g. Leishmania, Plasmodium, Trypanosoma ). Our research is the first to explore anti-amebic effects of Chinese rhubarb leaves' extract and isolated/synthetic anthraquinones on pathogenic Entamoeba . Abstract : Microbiology; Natural product chemistry; Parasitology; Pharmacology; Antimicrobial; Amebiasis; Antiparasitic; Natural products; Plant extracts